DESENVOLVIMENTO TECNOLÓGICO, CARACTERIZAÇÃO E AVALIAÇÃO IN VITRO DE DISPERSÕES SÓLIDAS CONTENDO ÁCIDO FERÚLICO - Franke, Fabiula Adriana (2014)
The ferulic acid has antioxidant, anti-inflammatory, antithrombotic, anticancer, neuroprotective, cardioprotective and photoprotective activity. However, despite these biological activities, its therapeutic usefulness is limited due to certain unfavorable physicochemical properties, especially the low aqueous solubility. It is classified as a Class II drug by the Biopharmaceutical Classification System and therefore its dissolution is a limiting step of absorption, may present bioavailability problems. Thus, considering the large number of pharmacological properties attributed to ferulic acid, the aim of this study was to develop and characterize solid dispersions containing ferulic acid, hydrophobic, a non-ionic surfactant (Poloxamer 407) and compare them in terms of improving the dissolution of ferulic acid. Solid dispersions were obtained by methods of crushing, kneading, co-evaporation, fusion, spray drying and freeze drying at concentrations of 10 and 20%. The formulations showed a yield between 38.6 and 80.2%. All formulations showed adequate amounts of efficiency of incorporation, greater than 80%. The solid dispersions were characterized by scanning electron microscopy, X-ray diffraction and spectroscopy in the infrared region in Fourier transform, whose results confirmed the acquisition of solid dispersions. The dissolution characteristics of the pure drug and the formulations were compared. Solid dispersions exhibited greater efficiency in improving the speed of dissolution of the ferulic acid, explainable by the effect of Poloxamer 407 surfactant. A highest increase of dissolving was obtained with the formulation obtained by the method of freeze drying at a concentration of 10%, with dissolution efficiency of 93.83%. The dissolution profiles showed the best fit to a monoexponential equation. These results suggest that the solid dispersions prepared with the use of Poloxamer 407, containing the drug, are strategies feasible in the pharmaceutical industry.